Calcification of the intracranial carotid artery and its relation to the clinical and angiographic picture: an angiographic classification of asteriosclerosis cerebri - Valter Seixas (Arquivos de Neuro-Psiquiatria)
Fifty six patients with arteriosclerosis cerebri confirmed by X-rays examinations were clinically and angiographically studied. Calcifications of the carotid artery were found predominantly in human beings between the ages of 55 and 65 and more often among men than among women, the proportion being 2.5 to 1. Nearly all arteriosclerotic patients with calcium deposits in the carotid artery showed several neurological and mental deficits, the most frequent initial symptoms being motor disturbances. Angiographic anormalities found in these patients can be classed into 3 groups: (a) grade I— wavy course of the cerebral vessels, small number of peripheral brain vessels, formation of small knots, prolonged circulation time, arteria cerebri anterior with angular form, straight course and broad caliber; (b) grade II— partial block, irregularities of wall and caliber, aneurysmal formations; (c) grade III— total block of some vessels of the carotid system preventing a generalized or localized cerebral blood supply. Grades II and III angiographic abnormalities were most often seen at the syphon and at the carotid bifurcation in the neck (site of predilection). Most patients with a progressive clinical course belonged to the I group. The course of the disease did not differ in patients with grades II and III angiographic changes since usually the illness had an apoplectiform onset. Arteriosclerotic degenerative irregularities within the layers of the arteries (up to atheromatous patches) may occur without reducing the arterial lumen. In such cases the patients may remain asymptomatic until there is a decompensation in the brain circulation due to many causes.